2012
DOI: 10.1371/journal.pone.0037839
|View full text |Cite
|
Sign up to set email alerts
|

Donor Age of Human Platelet Lysate Affects Proliferation and Differentiation of Mesenchymal Stem Cells

Abstract: The regenerative potential declines upon aging. This might be due to cell-intrinsic changes in stem and progenitor cells or to influences by the microenvironment. Mesenchymal stem cells (MSC) raise high hopes in regenerative medicine. They are usually culture expanded in media with fetal calf serum (FCS) or other serum supplements such as human platelet lysate (HPL). In this study, we have analyzed the impact of HPL-donor age on culture expansion. 31 single donor derived HPLs (25 to 57 years old) were simultan… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
103
2
7

Year Published

2013
2013
2022
2022

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 135 publications
(116 citation statements)
references
References 58 publications
4
103
2
7
Order By: Relevance
“…VBD concentrations added to culture medium ranged from 0.5 to 30% (54)(55)(56). Overall, VBD allowed for either, maintenance of MCS's fibroblast-like morphology (17,43,57), high proliferation (58-60), high colony-formation ability (52,61,62) and maintenance of multipotency (63)(64)(65)(66)(67). A linear dose-dependent response regarding medium concentration was not observed for evaluated VBD (54,56,68).…”
Section: Resultsmentioning
confidence: 97%
See 2 more Smart Citations
“…VBD concentrations added to culture medium ranged from 0.5 to 30% (54)(55)(56). Overall, VBD allowed for either, maintenance of MCS's fibroblast-like morphology (17,43,57), high proliferation (58-60), high colony-formation ability (52,61,62) and maintenance of multipotency (63)(64)(65)(66)(67). A linear dose-dependent response regarding medium concentration was not observed for evaluated VBD (54,56,68).…”
Section: Resultsmentioning
confidence: 97%
“…In the protocol to obtain the HPL, the Induction of fibrin clotting formation with calcium chloride (instead of thrombin) and posterior centrifugation provides a serum with the same profile of growing factor and cytokines than conventional HPL activated with thrombin, resulting in a serum without free of xenogeneic substances such as porcine thrombin (118). HPL supplemented without anticoagulants tend to form a translucent and viscous gel in 1 h providing a natural scaffold for MSC culture and expansion (61). This matrix, composed by a fibrin network, was biocompatible and biodegradable.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…When those steps are performed, they proceed to filtration through 0.22 um filters and addition of heparin (2U/ml) to the lysates 35,40,57 . This procedure is the most commonly found in the papers studied, but there are some authors which prefer performing chemical activation instead of thermic/mechanical activation and use of thrombin and/or calcium chloride 7,17,34,41,45,49 .…”
Section: Prp Activation Methodsmentioning
confidence: 99%
“…The allogenic preparations based on buffy coat also enable elimination of donor-to-donor variations by preparing mixed platelet isolates from multiple donors. The importance of the problem was highlighted by Lohmann et al, 38 who observed relationship between patient age and proliferation of MSCs.…”
mentioning
confidence: 99%